CD6 regulates T-cell responses through activation-dependent recruitment of the positive regulator SLP-76. - Hassan, N; Simmonds, S; Clarkson, N; Hanrahan, S; Puklavec, M; Bomb, M; Barclay, A; Brown, M (American Society for Microbiology, 2006)
Deciphering the role of lymphocyte membrane proteins depends on dissecting the role of a protein in the steady state and on engagement with its ligand. We show that expression of CD6 in T cells limits their responsiveness but that engagement by the physiological ligand CD166 gives costimulation. This costimulatory effect of CD6 is mediated through phosphorylation-dependent binding of a specific tyrosine residue, 662Y, in its cytoplasmic region to the adaptor SLP-76. A direct interaction between SLP-76 and CD6 was shown by binding both to a phosphorylated peptide (equilibrium dissociation constant [K(D)] = 0.5 muM at 37 degrees C) and, using a novel approach, to native phosphorylated CD6. Evidence that CD6 and SLP-76 interact in cells was obtained in coprecipitation experiments with normal human T cells. Analysis of human CD6 mutants in a murine T-cell hybridoma model showed that both costimulation by CD6 and the interaction between CD6 and SLP-76 were dependent on 662Y. The results have implications for regulation by CD6 and the related T-cell surface protein, CD5.